PENGARUH PERSEPSI SISWA ATAS KINERJA GURU DAN MOTIVASI BELAJAR TERHADAP PRESTASI MENULIS BAHASA INDONESIA PADA SISWA SMA SWASTA JAKARTA TIMUR - Tridays Repelita (Pujangga: Jurnal Bahasa dan Sastra, 2016)
ABSTRACTThis study aims to describe the influence of students' perceptions on teacher performance and motivation tolearn to write Indonesian at the private high school in East Jakarta. Motivation to learn is the impetus onstudents in the form of hard work and efforts in order to achieve better learning achievement baik.Metodeused in this research is quantitative correlational research. Therefore, the researchers only disclose databased on measurements of symptoms that already exist naturally in the respondents. The results of this studyis the first indicator) perseverance to learn, 2) curiosity, 3) Doing homework 4) flavor to excel, and 5) andnot easily discouraged.Keywords: perceptions of students, teacher performance, motivation to learn